Land cover, riparian zones and instream habitat influence stream fish assemblages in the eastern Amazon. Issue 2 (31st October 2018) - Montag, Luciano F. A.; Winemiller, Kirk O.; Keppeler, Friedrich W.; Leão, Híngara; Benone, Naraiana L.; Torres, Naiara R.; Prudente, Bruno S.; Begot, Tiago O.; Bower, Luke M.; Saenz, David E.; Lopez‐Delgado, Edwin O.; Quintana, Yasmin; et al.
Abstract: The Amazon rainforest has experienced rapid land‐use changes over the last few decades, including extensive deforestation that can affect riparian habitats and streams. The aim of this study was to assess responses of stream fish assemblages to deforestation and land cover change in the eastern Amazon. We expected that percentage of forest in the catchment is correlated with local habitat complexity, which in turn determines fish assemblage composition and structure. We sampled 71 streams in areas with different land uses and tested for relationships between stream fish assemblages and local habitat and landscape variables while controlling for the effect of intersite distance. Fish assemblage composition and structure were correlated with forest coverage, but local habitat variables explained more of the variation in both assemblage composition and structure than landscape variables. Intersite distance contributed to variance explained by local habitat and landscape variables, and the percentage of variance explained by the unique contribution of local habitat was approximately equivalent to the shared variance explained by all three factors in the model. In these streams of the eastern Amazon, fish assemblages were most strongly influenced by features of instream and riparian habitats, yet indirect effects of deforestation on fish assemblage composition and structure were observed even though intact riparian zones were present at most sites. Long‐term monitoring of the hydrographic basin, instream habitat and aquatic fauna is needed to test for potential legacy effects and time lags, as well as assess species responses to continuing deforestation and land‐use changes in the Amazon.